IDENTIFICATION OF PESTS AND DISEASES OF CAULIFLOWER PLANT (Brassica oleracea) IN JEPRONO, KARANGBANGUN, MATESIH, KARANGANYAR - Astari, Luthfiyyah Zulfaa; Nurhayati, Suci; Ningati, Rachma Kusuma; Nur’Aini, Citra Aisyah (Universitas Veteran Bangun Nusantara, 2024)
This research aims to identify pests and diseases that attack cauliflower (Brassica oleracea var. botrytis) plants in Jeprono Hamlet, Karangbangun Village, Matesih District, Karanganyar. This research is important to help farmers overcome pest and disease problems that can reduce the quality and quantity of cauliflower crops. The research methods used include field surveys, direct observation, and interviews with local farmers. Data collection was carried out by documenting symptoms of pest and disease attacks on cauliflower plants using a camera, as well as recording the results of observations in the sample fields. Data analysis was carried out descriptively qualitatively to identify the dominant types of pests and diseases. The research results show that there are four main types of pests that attack cauliflower, namely aphids (aphids), tritip caterpillars (Plutella xylostella), grasshoppers, and green caterpillars. Apart from that, one main type of disease was found, namely brown spot, which was caused by the bacteria Xanthomonas campestris. These pest and disease attacks have a significant impact on the health and productivity of cauliflower plants in the study area. It is hoped that this research can contribute to the development of more effective and environmentally friendly pest and disease control techniques for cauliflower farmers in the area, and can be applied in other areas with similar conditions.